Calculating the Bearing Capacity of Foundations near Slopes Based on the Limit Equilibrium and Limit Analysis Methods - Mulang Ye; Hua Tang (Buildings)
The ultimate bearing capacity of foundations near slopes is a widely discussed and researched topic in the field of geotechnics. Using the plane strain strength equation of the limit equilibrium and limit analysis methods, we established a new model for calculating the bearing capacity of foundations near slopes that can consider the intermediate principal stress, horizontal distance from the foundation to the shoulder of the slope, and roughness of the base. A formula of the ultimate bearing capacity of the foundation of foundations near slopes was derived, compared, and analyzed with that of finite element analysis software and other calculation methods. Comparative analysis was carried out using finite element analysis software and other calculation methods, and it was found that the obtained results are closer to the real solution of the ultimate bearing capacity of foundations near slopes. The intermediate principal stresses can improve the bearing capacity of foundations near slopes. The bearing capacity of foundations near slopes increases with the horizontal distance from the foundation to the slope and then remains constant. The results of this study can better reflect the actual ultimate bearing capacity of foundations near slopes and have certain theoretical significance for the optimal design of foundations near slopes.